A Petrological Estimation and Classification of the Lick2 in Kerang Ii Volcano of Jos Plateau State, Using Geothermometric and Empirical Approaches - Isah, Lekmang C.; Ifeanyi, Achuenu (Sigma&Mu: Journal of Mathematics Education, Mathematics, Statistics and Data Science, 2025)
Abstract: The KERANG II volcano on the Jos Plateau, Plateau State, Nigeria, is part of a series of significant volcanic activity and provides a unique window into understanding regional magmatic and geodynamic processes. Volcanic rocks in this area are often associated with geochemical and petrological anomalies, making it an important subject for in-depth scientific investigation. To understand the evolution and composition of the Earth's interior, detailed characterization of igneous rocks is fundamental. This study aims to estimate and classify the petrology of LICK2 samples from KERANG II Volcano, Jos Plateau, Plateau State, Nigeria, by applying Bowen and Goldschmidt's concepts through Geothermometric and Empirical approaches. The analysis shows that, based on a mathematical framework combining Bowen and Goldschmidt's rules, LICK2 samples are classified as members of the gabbro clan. Minerals estimated using the empirical approach include Augite (Basic Clinopyroxene), Hyalosiderite (Basic Olivine), Labradorite (Basic Plagioclase), and Ulvospinel (Iron Ore). The gabbro clan includes basalt, dolerite, norite, scoria, and gabbro. Empirically, LICK2 samples from KERANG II Volcano show characteristics of gabbro clan rocks with alkaline basaltic magma types. This study successfully establishes a "mathematical relationship" between Bowen and Goldschmidt's concepts, providing a concise explanation of the mineral formation of KERANG II Volcano rocks, from the beginning to the end of crystallization. Keywords: Bowen; Geology and Rock; Goldschmidt; Numerical, Empirical